Pontoniine shrimps (Decapoda: Palaemonidae) from the island of Socotra, with descriptions of new species of Dactylonia Fransen, 2002 and Periclimenoides Bruce, 1990 - Bruce, A. J. (Zootaxa, 2006)
The present report provides information on 20 pontoniine shrimp taxa from the island of Socotra, collected by Dr Michael Apel, including two new species, of the genera Dactylonia Fransen and Periclimenoides Bruce. Thirteen species are reported from Yemen for the first time, 8 are newly recorded from the north western Indian Ocean. The record of Periclimenoides is the first occurrence of this genus in the western Indian Ocean. The number of pontoniine shrimps known from the north west Indian Ocean is now increased from 32 to 44 taxa.